Different AHO phenotype in a Chinese family with a novel GNAS missense variant: a case report - Qing Zhou; Bin Liang; Qing-Xian Fu; Hui Liu; Chao-Chun Zou (BMC, 2022)
Abstract Background Albright's hereditary osteodystrophy (AHO) is an inherited disorder which is caused by an inactivating variant in the GNAS gene. AHO appears associated to either pseudohypoparathyroidism 1a (PHP1a) when GNAS gene is maternally inherited or to pseudo-pseudohypoparathyroidism (PPHP) when it is paternally inherited. We describe the clinical and biochemical characteristics of two patients, a boy and his mother with a novel heterozygous missense variant of GNAS gene. Case presentation The boy presented with typical AHO phenotype (early-onset obesity, round face, short neck, shortened fifth metacarpal bone, developmental retardation, but without short stature and subcutaneous calcifications), multiple hormone resistance including PTH, TSH and ACTH, and mild calcification in the right basal ganglia. The mother only presented with brachydactyly and short stature, without hormone resistance and other signs of AHO. Whole-exome sequencing identified in the son and his mother a novel heterozygous missense variant (p. Val375Leu) in exon 13 of GNAS gene. The diagnosis of PHP-1a for the son and PPHP for the mother were confirmed. Conclusion This study further expands the spectrum of known GNAS pathogenic variants, and also demonstrates the heterogeneous phenotype of AHO due to a novel GNAS pathogenic variant.